Targeting the hypoxic expression of epidermal growth factor receptor - Alamoudi, Abdulmohsin (2021)
Investigating translation regulation of epidermal growth factor receptor (EGFR) is a growing concern in the context of advanced breast cancer. The 5’ untranslated region (UTR) of EGFR mRNA contains an internal ribosome entry site (IRES) that permits hypoxic expression. This allows targeting of the expression of EGFR in breast cancer cells under hypoxia and other stress conditions. Here we describe the role of the EGFR IRES in mediating protein expression under stress conditions commonly associated with malignant growth including DNA damage. The requirement for DDX3, a DEAD-box RNA helicase, was also investigated in terms of regulating the mRNA translation of EGFR via its 5’ UTR. In addition, this study seeks to obtain data with regards to the feasibility of targeting the hypoxic expression of EGFR using the antisense technology and polymeric delivery systems.